KONSTRUKSI BERITA KONFLIK PASCA BENCANA ALAM PADA HARIAN KOMPAS - Dian Muslimah (Jurnal Sosiologi Nusantara, 2015)
Natural disasters often lead to social change, and the changes of structural society often lead to post-disaster conflicts in the community. When a natural disaster occurs, the mass media became one of the main elements that preach it to the outside world through a text message. While the news is the result of social construction that always involving views, ideologies and values. Construction performed by mass media does not take place in an empty space, but it is loaded with interests especially for the news of conflict, because it contains a high value news. This study aimed to determine the focus on post disaster situations on Kompas news, and how Kompas taking up the post-conflicts on Padang earthquake within community through text message construction. This study is focused on the news text in the Kompas Daily that contain post earthquake conflict during October, 2009, and will be analyzed using critical discourse analysis of Teun Van Dijk's three levels of analysis methods. Seen from the analysis result of post-disaster conflict news text that occurred in Padang, the post- disaster conflict news had conducted by Kompas daily with a great caution. News themes of conflict that raised were not presented the opinion of both parties who are in conflict in the same text news. From the social analysis of this research, conflicts regarding to natural disaster relief as happened in West Sumatra were included in the conflict caused by differences in the aspirations between parties, which led to negative attitudes and perceptions to other party. While the result of social cognition analysis to Kompas, found that past experiences lead Kompas applying style crab journalism that being cautious, especially in conflict review. Kompas Daily also apply transcendental humanism principles to make it accepted by all parties. Moreover, the presence of Standardization Language team (BP) that standardize the language, makes the language style used by Kompas become more delicate and polite. In the earthquake disaster that occurred in Padang, the conflict was happened vertically, between the community and government caused by the unequal distribution of aid. By the factors, conflicts are often caused by the process of social change are not equally experienced by people in the community structure, the social changes experiencing by the post-disaster community are caused by unexpected pressure beyond human capability as well as the factor of interest (of the government/ authorities) which further leads to survival instinct. But apparently behind the process of social change that led to conflict, post-disaster conflict was caused by the society attempts to get back the means of production due to the changing mode of production caused by natural disasters. This effort makes a vertical conflict between the government as a resource owners and the community as a group that does not have the resources, which leads to collective action such as protests against the policies of aid distribution that are deemed unfair.Keywords : Disasters, Conflicts, Critical Discourse Analysis